2019
DOI: 10.1088/1361-6641/aafa4c
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of indium in single crystal zinc oxide: a comparison between group III donors

Abstract: Dopant diffusion of indium (In) in single crystal zinc oxide is studied by secondary ion mass spectrometry and is interpreted using a reaction-diffusion model that invokes predictions from density functional theory (DFT). An apparent activation energy of 2.2 eV is obtained for the diffusion of In, when the local Fermi-level position is about 0.2 eV below the conduction band edge. The diffusion of In is found to be significantly faster that that reported for the other group III donors, aluminum and gallium, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…These observed changes in the integrated PL intensity indicate that the entire volume of material probed with nearband gap excitation (λ exc = 360 nm) is affected by the In implantation. This does not necessarily mean the probing depth is only the 200 nm depth of implanted In ions, because intrinsic defects created during implantation could diffuse deeper into the material during annealing [36][37][38].…”
Section: A Photoluminescence Spectroscopymentioning
confidence: 99%
“…These observed changes in the integrated PL intensity indicate that the entire volume of material probed with nearband gap excitation (λ exc = 360 nm) is affected by the In implantation. This does not necessarily mean the probing depth is only the 200 nm depth of implanted In ions, because intrinsic defects created during implantation could diffuse deeper into the material during annealing [36][37][38].…”
Section: A Photoluminescence Spectroscopymentioning
confidence: 99%
“…a) Solid-solubility-limit as a function of temperature for n-type dopants (Ga, Al, In) in single-crystalline ZnO, using data taken from references. [22][23][24] b) Dopant diffusion lengths for Ga, Al, and In in ZnO at 900 °C as a function of annealing time. [23,25,26] The dashed orange lines indicate typical annealing times for furnace annealing (FA) and laser annealing (LA).…”
Section: Methodsmentioning
confidence: 99%
“…Their modeling of the measured Ga diffusion profiles revealed that the dominant diffusion mechanism is consistent with zinc (Zn) vacancy (V Zn ) mediation via the formation and dissociation of Ga Zn V Zn complexes with substitutional Ga at the Zn sub-lattice (Ga Zn ). [22] The temperature-dependent SSL of Ga, aluminum (Al), and indium (In) in ZnO was determined by Sky et al with a reactiondiffusion-type model, [22][23][24] which is based on Fickian diffusion plus a nonlinear reaction term. More theoretical background can be found in refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common material in TCOs is indium tin oxide (ITO). However, efforts are being made to find alternative materials with low resistivity and high transmittance to replace ITO because of the high cost of indium and the diffusion problem [1,2]. As the device becomes smaller, the electrode thickness must be as thin as possible to maintain low resistance.…”
Section: Introductionmentioning
confidence: 99%